PENERAPAN APLIKASI PENGINGAT JADWAL KEGIATAN PENGGABUNGAN WAKTU DAN TANGGAL BERBASIS ANDROID - Muhammad Ridhan Maulana Nanda; Ines Heidiani Ikasari (CV. Multi Kreasi Media, 2023)
Information Technology which is currently commonly used by many people, between using Computer Technology and Smartphone Technology Along with the rapid development of Information Technology. The main problem faced today is that Smartphone users sometimes there are some people or students who forget to manage and keep their daily activities, especially in remembering their daily tasks or activities. An application that can help student agendas as well as for management in reminding these students wherever and whenever they are together with their Smartphones this research aims to provide notifications in the form of text other than sounds on smartphones and become a solution for students to make it easier for students to remember the entire schedule of activities. The application development method used in this study is the Waterfall Model. This thesis will describe the activities produced at each stage of development. So it is necessary that this application will be a solution for students to improve student discipline towards time in considering that the entire activity schedule gets 75% results. In addition, by simply adding the status of activities to this reminder application will be useful for students to get 85% results, the Android-based time and date combination activity reminder application will provide information that has been previously inputted on the activity schedule to get 75% results.